1986
DOI: 10.1159/000469312
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of Membrane-Associated Phospholipase A(2) of Human Spleen

Abstract: Membrane-associated phospholipase A(2) was purified to homogeneity from human spleen. The enzyme was solubilized from the particulate fraction by the addition of KBr, and purified by reverse-phase high-performance liquid chromatography. The estimated molecular weight of the enzyme was 14,000. The enzyme had a pH optimum around 9.5, required the presence of Ca^2+ for its activity, and hydrolyzed phosphatidylethanolamine more efficiently than phosphatidylcholine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…In 1983, Eskola et al [8] and we ourselves [9] independently developed a specific im munoassay for human pancreatic PLA2 (P-PLA2), and later we showed that the ra dioimmunoassay (RIA) for human P-PLA2 did not react with PLA2 from the human spleen [10]. Uhl et al [11] have reported an increase in serum catalytic PLA2 activity in patients with multiple injuries.…”
Section: Human M-pla2mentioning
confidence: 98%
“…In 1983, Eskola et al [8] and we ourselves [9] independently developed a specific im munoassay for human pancreatic PLA2 (P-PLA2), and later we showed that the ra dioimmunoassay (RIA) for human P-PLA2 did not react with PLA2 from the human spleen [10]. Uhl et al [11] have reported an increase in serum catalytic PLA2 activity in patients with multiple injuries.…”
Section: Human M-pla2mentioning
confidence: 98%
“…Until recently, two genetically distinct isoenzymes, exocrine PLA2 (secreted in pancreatic juice) and intracellular PLA2 (contained in the cytosol and membrane-associated fraction), have been recognised in humans (Vadas & Pruzanski, 1986;Nakaguchi et al, 1986). In the membrane fraction of human spleen cells the existence of a PLA2, which does not react with anti-human P-PLA2 antibody, has been demonstrated (Nakaguchi et al, 1986). Further purification and subsequent sequencing of this enzyme revealed that it belongs to the Group-I1 PLA2 (Kanda et al, 1989).…”
mentioning
confidence: 99%
“…In addition, a calcium-dependent PLA2 is thought to be one of the most important enzymes regulating the release of arachidonic acid from membrane phospholipids (Lands, 1968; Van den Bosh, 1980). Until recently, two genetically distinct isoenzymes, exocrine PLA2 (secreted in pancreatic juice) and intracellular PLA2 (contained in the cytosol and membrane-associated fraction), have been recognised in humans (Vadas & Pruzanski, 1986;Nakaguchi et al, 1986). In the membrane fraction of human spleen cells the existence of a PLA2, which does not react with anti-human P-PLA2 antibody, has been demonstrated (Nakaguchi et al, 1986).…”
mentioning
confidence: 99%
“…PLA, from other tissues is inhibited by guanidinobenzoates and amidino derivatives (Hesse and Lankisch, 1984;Nakaguchi et al, 1986;Pepinsky et al, 1986) and indomethacin (Drummond and Olds-Clarke, 1986;Bonney et al, 1988). These agents are generally regarded as acrosin and cyclooxygenase inhibitors.…”
Section: Introductionmentioning
confidence: 99%